Emerging trends of BCG immunotherapy for bladder cancer in last decade: a bibliometric and visualization analysis - Chen, Xingfeng; He, Fang; Zhang, Wenjin; Fu, Yao; Cao, Zhiqin (Frontiers in Oncology, 2023)
Background: One of the milestones in bacterial-mediated therapy for cancer, Bacillus Calmette-Guerin (BCG) has been used to treat bladder cancer (BC) for more than 30 years. BCG immunotherapy is now the standard of care for high-grade non-muscle invasive bladder cancer (NMIBC) following transurethral resection. Methods: We searched the Web of Science core collection (WoSCC) database and used bibliometric methods through CiteSpace (version 5.1.R6), VOSviewer (version 1.6.18) and R-Bibliometrix (version R 4.2.1) to analyze and discuss the current status and trends of BCG therapy of BC from 2012 to 2021 in terms of co-occurrence, co-polymerization and visualization. Results: A total of 2476 publications were found, with the majority coming from the United States and China. Over the last decade, overall yearly outputs have increased fivefold, from 117 papers in 2012 to 534 records in 2021. Most publications were produced by the University of Texas System. The authors, Ashish M. Kamat of the University of Texas-MD Anderson Cancer Center in the United States, and Shahrokh F. Shariat of Weill Cornell Medical College, were pioneers in this field with the most publications. The journals, Urologic Oncology Seminars and Original Investigations, Cancers and Frontiers in Oncology, have published a dramatic increase in the number of articles, and tumor and urology nephrology research directions have received the most attention from journals. Furthermore, recent research has concentrated on muscle-invasive bladder cancer (MIBC). BCG therapy mechanism, BCG dose and strains, targeted therapy and immune checkpoint inhibitors (ICIs) for BC were attractive research contents, with ICIs (PD-1, PD-L1) being the most popular study point in recent years. With more research on tumor immunology, screening for more reliable biomarkers for precision treatment, and the development of combination regimens of ICIs, targeted treatment of BC stem cells, and personalized BC therapies may be promising areas of immunotherapy research in the coming years. Conclusions: The results of this bibliometric study can provide the current status and research trends of BCG therapy for BC in the last decade, and also further complements the research content of bacterial-mediated cancer therapy.